Propagation of Gevrey regularity for solution of non-cutoff Boltzmann equation. (October 2022) - Liu, Lvqiao
Abstract: In this paper, we focus on the Gevrey regularity of the solution to non-cutoff Boltzmann equation. We prove the propagation of Gevrey regularity for γ < 0, this extends the result of Desvillettes et al. (2009) on the case of Maxwellian molecules. Our proof relies on the elementary L 2 weighted estimate.